Hypertension screening, awareness, treatment, and control: a study of their prevalence and associated factors in a nationally representative sample from Nepal - Raja Ram Dhungana; Zeljko Pedisic; Meghnath Dhimal; Bihungum Bista; Maximilian de Courten (Taylor & Francis Group, 2022)
Background The growing burden of hypertension is emerging as one of the major healthcare challenges in low- and middle-income countries (LMICs), such as Nepal. Given that they are struggling to deliver adequate health services, some LMICs have significant gaps in the cascade of hypertension care (including screening, awareness, treatment, and control). This results in uncontrolled hypertension, placing a high burden on both patients and healthcare providers. Objective The objective of this study was to quantify the gaps in hypertension screening, awareness, treatment, and control in the Nepalese population. Methods We used the data from a pooled sample of 9682 participants collected through two consecutive STEPwise approach to Surveillance (STEPS) surveys conducted in Nepal in 2013 and 2019. A multistage cluster sampling method was applied in the surveys, to select nationally representative samples of 15- to 69-year-old Nepalese individuals. Prevalence ratios were calculated using multivariable Poisson regression. Results Among the hypertensive participants, the prevalence of hypertension screening was 65.9% (95% CI: 62.2, 69.5), the prevalence of hypertension awareness was 20% (95% CI: 18.1, 22.1), the prevalence of hypertension treatment was 10.3% (95% CI: 8.8, 12.0), and the prevalence of hypertension control was 3.8% (95% CI: 2.9, 4.9). The unmet need of hypertension treatment and control was highest amongst the poorest individuals, the participants from Lumbini and Sudurpaschim provinces, those who received treatment in public hospitals, the uninsured, and those under the age of 30 years. Conclusions The gaps in the cascade of hypertension care in Nepal are large. These gaps are particularly pronounced among the poor, persons living in Lumbini and Sudurpaschim provinces, those who sought treatment in public hospitals, those who did not have health insurance, and young people. National- and local-level public health interventions are needed to improve hypertension screening, awareness, treatment, and control in Nepal.